Emotional Stability and Adjustment in Adolescents: A Comparative Study of Advantaged and Disadvantaged Groups (Indian Journal of Psychology & Education, 2018)
Emotional stability is the capacity to maintain one’s emotional tolerance under stressful circumstances. It is a state of an individual that enables him or her to have appropriate feelings about common experiences and acts in a rational manner. Emotional stability refers to the concept of emotional behaviour that reflects the emotional development and emotional stability of human beings which enable them to keep their emotions stable and under control even in extreme difficult situations. Adjustment is an important aspect and requirement too for almost all circumstances and situations and those individuals who have ability to adjust everywhere are known as well adjusted person and those who fail to be adjust in some or difficult condition are known as maladjusted. Present study was conducted with the objective of examining the differences in emotional stability and adjustment between students of advantaged and disadvantaged groups. Further it was also intended to study the gender differences in terms of emotional stability and adjustment of advantaged and disadvantaged groups. Emotional stability test for children and adjustment inventory were administered on 120 students. The purposive random sampling technique was used to select advantaged and disadvantaged groups of adolescents from various schools of Aligarh District. Data were analyzed using t test. Results clearly showed that the advantaged groups of adolescent students were having higher level of emotional stability than disadvantaged groups of adolescent students. But both the groups of students showed almost same level of adjustment and from the point of view of gender differences adolescent boys were found to be highly emotionally stable and well adjusted than adolescent girls.